2005
DOI: 10.1159/000084294
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Sonohysterography in Infertile Patient Work-Up: A Comparison with Transvaginal Ultrasonography and Hysteroscopy

Abstract: Objective: The aim of this comparative study was to evaluate the accuracy of transvaginal ultrasonography (TVU), sonohysterography (SHG) with sterile saline solution compared to hysteroscopy in the diagnosis of intrauterine pathology in a population of infertile patients before an in vitro fertilization (IVF) program. Patients/Methods: 98 infertile patients with a mean age of 33.9 years (range 27–41) underwent TVU assessment and SHG with sterile saline solution immediately followed by hysteroscopy. Results: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 58 publications
(32 reference statements)
5
16
0
2
Order By: Relevance
“…10,14,15 The overall low sensitivity of SIS in the present study can be partially explained by high incidence of intrauterine synechiae (36.36%) and their low detection rate by SIS (16.7%). In the present study out of eight patients with intrauterine synechiae five had mild lesions.…”
Section: Discussionmentioning
confidence: 66%
“…10,14,15 The overall low sensitivity of SIS in the present study can be partially explained by high incidence of intrauterine synechiae (36.36%) and their low detection rate by SIS (16.7%). In the present study out of eight patients with intrauterine synechiae five had mild lesions.…”
Section: Discussionmentioning
confidence: 66%
“…15 Regarding HSG they found a sensitivity, specificity, PPV and NPV of 98%, 94%, 95% and 98% respectively. The sensitivity of HSG in present study was 90%, specificity of 100%, a PPV of 100% and NPV of 66.6%.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, among the diagnostic methods, hysterescopy gives the highest diagnostic efficacy in detecting endometrial polyps (Elfayomy et al, 2012). It also show great accuracy in diagnosis of focal endometrial pathologies which are hardly recognized by ultrasonography, especially thickenned endometrium that hidden the intracaviter lession (Ragni et al, 2005;Schmidt et al, 2009). Makris et al (2007) showed that hysteroscopy with guided biopsy is the most common comparator for other techniques to diagnose polyps as it offers the highest sensitivity and specificity for conservative measures.…”
Section: Discussionmentioning
confidence: 99%